2018
DOI: 10.3389/fpsyt.2018.00526
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Associations of Modifiable Lifestyle Factors With Positive Depression-Screen Over 2.5-Years in an International Cohort of People Living With Multiple Sclerosis

Abstract: Background: Depression is common and has a significant impact on quality of life for many people with multiple sclerosis (MS). A preventive management approach via modification of lifestyle risk factors holds potential benefits. We examined the relationship between modifiable lifestyle factors and depression risk and the change in depression over 2.5 years.Methods: Sample recruited using online platforms. 2,224 (88.9%) at baseline and 1,309 (93.4%) at 2.5 years follow up completed the necessary survey data. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 71 publications
1
17
1
1
Order By: Relevance
“…Both antiinflammatory and other diets were associated with improved mobility, consistent with proposed neuroinflammatory and microbiota-gut-brain-axis disease mechanisms. Though studies have reported associations between diet quality and MS-specific diets with lower depression and fatigue respectively [24,25], we did not observe associations in these symptom subdomains. Discrepancies may be attributable to outcome measure tools in addition to potential additive benefits of adhering to multiple lifestyle behaviors.…”
Section: Discussioncontrasting
confidence: 99%
“…Both antiinflammatory and other diets were associated with improved mobility, consistent with proposed neuroinflammatory and microbiota-gut-brain-axis disease mechanisms. Though studies have reported associations between diet quality and MS-specific diets with lower depression and fatigue respectively [24,25], we did not observe associations in these symptom subdomains. Discrepancies may be attributable to outcome measure tools in addition to potential additive benefits of adhering to multiple lifestyle behaviors.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, we would draw the conclusion that one parameter (sample size or item number) can be small, given the other is sufficiently large. What is the implication, what should change now. The recent trend in medicine to use very short scales (as low as two items) (see, eg, the works of Taylor et al and Staples et al) seems critical in light of the present simulation results. Neither IRT nor CTT can be expected to yield valid results in such short scales. …”
Section: Abbreviationsmentioning
confidence: 75%
“…For example, in a 7-year follow-up of the Komo-Ise cohort study, Tanaka et al [ 16 ] showed that heavy alcohol consumption and physical inactivity were associated with a higher prevalence of depression in Japanese men, and obesity, inadequate sleep, and smoking were associated with a higher prevalence of depression in Japanese women. In an international cohort study of patients with muscle sclerosis, Taylor et al [ 17 ] showed that healthy lifestyles, including moderate alcohol intake, being a non-smoker, diet quality, no meat or dairy intake, vitamin D supplementation, omega 3 supplement use, regular exercise, and meditation at baseline, were associated with lower incidences of depression.…”
Section: Introductionmentioning
confidence: 99%